Seasonal variation in giraffe population density and abundance in the Tsavo landscape, Kenya - Njueini, JK; Mwangi, EM; Montgomery, RA (Wiley, 2023)
The giraffe population is thought to vary seasonally in the Tsavo landscape of Kenya, but little data exists to establish if there indeed exists any variability. This study examined the impact of seasonal variation on the giraffe population in the Tsavo landscape. We conducted road transect counts and found 2683 and 3295 giraffes during the wet and dry seasons, with mean KAI and density of 0.19 ± 0.01 and 1.20 ± 0.435/km2, respectively. The giraffe population did not vary significantly between seasons, age and sex. The parks had more giraffes during the wet season compared to the dry season, while the reverse was true for Rombo and Taita ranches. No giraffes were sighted in South Kitui National Reserve.